Diseño de un plan de importación de atún rayado en el municipio de plato magdalena en tiempos de emergencia sanitaria de covid 19 (2021)
The objective of this research article is to design an import plan for grated tuna for the municipality of Plato Magdalena in time of a health emergency of covid-19. This implies the search for international suppliers, search for potential customers who can acquire the product in a significant volume. This is done because the company Quilla Import & Export is in an imminent decline in its finances, so it was necessary to design a business idea that would allow in times of health emergency to recover and be able to bill significantly. After this aforementioned process, the investigation found that the business idea is minimally viable using basic financial parameters such as the cost benefit calculation, which yielded a good result for the investor confidence of the company.